If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + -1b) = b Reorder the terms: 4(-1b + x) = b (-1b * 4 + x * 4) = b (-4b + 4x) = b Solving -4b + 4x = b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-1b' to each side of the equation. -4b + -1b + 4x = b + -1b Combine like terms: -4b + -1b = -5b -5b + 4x = b + -1b Combine like terms: b + -1b = 0 -5b + 4x = 0 Add '-4x' to each side of the equation. -5b + 4x + -4x = 0 + -4x Combine like terms: 4x + -4x = 0 -5b + 0 = 0 + -4x -5b = 0 + -4x Remove the zero: -5b = -4x Divide each side by '-5'. b = 0.8x Simplifying b = 0.8x
| 8-4*x=4-6*x | | 26-42-(-37)+(-15)= | | -5+6x=10+4x | | 3(2x-4)=x+8 | | 2-3(x+4)=2(4-3x) | | 3/4x+6/8x=36/12 | | 3x+5-x=-17 | | 2x^(1/2)-9x^(1/4)+6=0 | | 4.9+z=-9 | | 4y-4x-7y+7x= | | x+10+x+x=13+x | | p=2(6)+2(4) | | 6-3x=-37 | | 5p/7-8=-43 | | 3(-4+x)=4x+(1/3) | | 2t+10-5= | | 9a-6=3a+3a+4+4a | | 3x+2+4y+2+3y= | | 9/7=11/8x+3 | | -7x=-5x-10 | | 4x+7-3x+6= | | 4(34+9x)+16x=32 | | 5x+2(3x-7)=-20+11x+6 | | 10x+x= | | -12b+6b-4b= | | 3/4=x/4 | | 9(16x+4y)+34=32 | | 25m^2-25= | | t=13+x | | 9+2/5=29-11/7 | | 2/-5=6/t | | 3+3x=-6+2x |